Low‐temperature thermochronology of francolite: Insights into timing of Dead Sea Transform motion. (10th April 2019) - Kohn, Barry; Weissbrod, Tuvia; Chung, Ling; Farley, Ken; Bodorkos, Simon
Abstract: Cambrian siliciclastic sequences along the Dead Sea Transform (DST) margin in southern Israel and southern Jordan host both detrital fluorapatite [D‐apatite] and U‐rich authigenic carbonate‐fluorapatite (francolite) [A‐apatite]. D‐apatite and underlying Neoproterozoic basement apatite yield fission‐track (FT) data reflecting Palaeozoic–Mesozoic sedimentary cycles and epeirogenic events, and dispersed (U–Th–Sm)/He (AHe) ages. A‐apatite, which may partially or completely replace D‐apatite, yields an early Miocene FT age suggesting formation by fracturing, hydrothermal fluid ascent and intra‐strata recrystallisation, linked to early DST motion. The DST, separating the African and Arabian plates, records ~105 km of sinistral strike‐slip displacement, but became more transtensional post‐5 Ma. Helium diffusion measurements on A‐apatite are consistent with thermally activated volume diffusion, indicating Tc ~52 to 56 ± 10°C (cooling rate 10°C/Ma). A‐apatite AHe data record Pliocene cooling (~35 to 40°C) during the transtensional phase of movement. This suggests that timing of important milestones in DST motion can be discerned using A‐apatite low‐temperature thermochronology data alone.